2015
DOI: 10.1016/j.neulet.2014.11.029
|View full text |Cite
|
Sign up to set email alerts
|

Direction of magnetoencephalography sources associated with feedback and feedforward contributions in a visual object recognition task

Abstract: Identifying inter-area communication in terms of the hierarchical organization of functional brain areas is of considerable interest in human neuroimaging. Previous studies have suggested that the direction of magneto- and electroencephalography (MEG, EEG) source currents depends on the layer-specific input patterns into a cortical area. We examined the direction in MEG source currents in a visual object recognition experiment in which there were specific expectations of activation in the fusiform region being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 39 publications
3
24
0
Order By: Relevance
“…It is possible that this finding reflects a summation of bottom-up excitatory processes of neural activity. This conclusion is in accordance with recent evidence from magnetoencephalography in the visual modality, suggesting that the P1 response corresponds to feedforward driven (bottom-up) activity, whereas the later N1 response might reflect feedback (top-down) effects [32]. At the time of the P1, sLORETA revealed largely identical areas in both tasks, namely a region around auditory cortex, posterior superior temporal gyrus, insula, and inferior parietal lobule (cf.…”
Section: Discussionsupporting
confidence: 91%
“…It is possible that this finding reflects a summation of bottom-up excitatory processes of neural activity. This conclusion is in accordance with recent evidence from magnetoencephalography in the visual modality, suggesting that the P1 response corresponds to feedforward driven (bottom-up) activity, whereas the later N1 response might reflect feedback (top-down) effects [32]. At the time of the P1, sLORETA revealed largely identical areas in both tasks, namely a region around auditory cortex, posterior superior temporal gyrus, insula, and inferior parietal lobule (cf.…”
Section: Discussionsupporting
confidence: 91%
“…The different sources of the brain component are consistent with the path analysis we conducted in order to investigate the spatio-temporal unfolding of the mismatch effect. In our modeling approach, we assumed that visual object recognition is hierarchically organized in a sequence of cortical activation involving both (feedforward) input from early to higher-level areas, and top-down facilitation (feedback) from frontal regions to temporal regions [ 78 , 79 ] and even occipital regions [ 80 ]. This hypothesis has already been validated using dipole modeling of EEG/MEG data [ 79 ], or dynamic causal modeling of fMRI data [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our modeling approach, we assumed that visual object recognition is hierarchically organized in a sequence of cortical activation involving both (feedforward) input from early to higher-level areas, and top-down facilitation (feedback) from frontal regions to temporal regions [ 78 , 79 ] and even occipital regions [ 80 ]. This hypothesis has already been validated using dipole modeling of EEG/MEG data [ 79 ], or dynamic causal modeling of fMRI data [ 81 ]. Along those lines, Garrido et al, [ 78 ] showed that backward connections mediate late components of event-related mismatch responses in an oddball paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…Gamma synchrony is thought to represent a specific kind of activation, and is believed to play an important role in the synchronization within functional units, integrating proximate or distant functional units, and can do so in a time-locked or phase-locked manner (Başar et al, 1999 ). Gamma activation has been shown to relate to a number of cognitive processes, including object recognition (Schadow et al, 2009 ; Castelhano et al, 2014 ; Ahlfors et al, 2015 ), memory types (Başar et al, 1999 , 2001 ; Nyhus and Curran, 2010 ; Roux and Uhlhaas, 2014 ; Heusser et al, 2016 ; Després et al, 2017 ), and conscious processing (Aru and Bachmann, 2009 ; Doesburg et al, 2009 ; Luo et al, 2009 ; Steinmann et al, 2014 ; Cabral-Calderin et al, 2015 ; Tu et al, 2016 ). Most notably, gamma has been linked to the functional coupling—or binding—of brain regions that ensures integration and appropriate processing of information (Klimesch et al, 2010 ; Ehm et al, 2011 ; Schneider et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%